TESTICULAR ELASTOGRAPHY IN PATIENTS WITH VARICOCELE AND INFERTILITY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
We wish to evaluate the performance of Real-time Elastography (RTE) in assessing the effect of varicocele on testicular interstitial elasticity as well as in forecasting the effect of varicocele on sperm motility.
Keywords: Elastography, Sono- elastography, Ultrasound, Scrotum, Testis